Analysis and Design of a Non-Invasive Wood Moisture Sensor - Avalos, Mariel (2023)
This paper presents an analysis and design of moisture sensor for South American wood species. The proposed sensor is designed to non-invasively measure the estimated moisture content of a piece of wood based on its dielectric properties. The article provides the methodology for designing and developing an inter-digital capacitance sensor, along with its implementation using a multi-stage amplifier circuit.